DESAIN DIDAKTIS MELALUI NAÃVE GEOMETRI UNTUK MENGATASI HAMBATAN EPISTEMOLOGIS DALAM PERSAMAAN KUADRAT DI SMA - Putri, Nurkhasanah Sukimin; Hartoyo, Agung; Jamiah, Yulis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractResearch backgrounded by the existence of the epistemological obsclae of students in understanding the matter of quadratic equations. The method used was didactic design research including didactic design analysis before learning, metapedadidaktis analysis and retrospective analysis. The stage of didactic design analysis before learning was done on IXB IPS class to 22 students to found out the epistemological obsclae of students in the quadratic equation. After knowing the obsclae that the students had, made a design learning to overcome students epistemological obsclae. The validated design was applied to the students of XB class at Ma'arif Ketapang Senior High School, amounting to 18 students. The next stage was Metapedadidaktis analysis, that was analyzing a pedagogical didactic situation based on the response experienced by the students. The last stage was retrospective analysis that was to analyze how far the implementation of didactic design with learning that goes on when didactic design was applied. The didactic design developed includes lessons plan, activity sheet of learners and activities which was conducted there was using the historical approach of naïve geometry in solving the problem of quadratic equations, and find the general formula to solve the problem of quadratic equations. The result of the research was generally in the form of didactic design developed with historical approach of naïve geometry to overcome the epistemological barriers in the matter of quadratic equations. Keywords: Design Didactial, Naïve Geometry, Epistemological obstacle